Toxocara cati infestation in a Leopardus pardalis specimen in Colombia; case report - Muñoz-Rodriguez, Fabián Andrés (2021)
It is reported the case of a Leopardus pardalis specimen, male, 15.6 kg body weight, found with partial decomposition in a road in the rural sector of the municipality of Arauca, Colombia. At necropsy, 36 parasitic forms of nematodes were found, with an approximate length of 3.4 cm, which were identified as Toxocara cati by the presence of lateral fins at the cervical end, the presence of three lips and a ringed cuticle. This is the first report in Colombia of the parasitic species in this wild feline, indicating that the species L. pardalis may be a potential carrier and disseminator of T. cati.